Violência baseada na expressão de gênero e de orientação sexual na Educação Física: professores e professoras como agentes de prevenção - Freitas, Milena de Bem Zavanella (2021)
School violence is a growing and multiple phenomenon that affects people's lives in different ways. Scientific production shows that the expression of gender and sexual orientation is related to the increased risk of being a victim of violence and bullying in schools. This research promotes a dialogue between scientific evidence and the collaboration of Physical Education teachers for the prevention of violence, focusing on gender and sexual orientation. Therefore, the general objective was to structure fundamental knowledge that corresponds to training programs for Physical Education teachers, in order to qualify agents for preventing violence, especially violence based on gender and sexual orientation, through dialogue between Physical Education teachers and the scientific contributions to solving these problems. The articulation between the results of this research and scientific productions on violence allows us to claim the presence of specific knowledge in the initial training process, as well as the promotion of community training for prevention work. Among the fundamental knowledge for the prevention of violence, this research highlights the importance of interactions and socialization processes for the maintenance or overcoming of violence. Through preventive socialization, it is possible to educate children and young people, especially peer groups and friends, as essential factors in the work of preventing and overcoming violence. We also consider that the contents of Physical Education can be treated by the principles of dialogic learning and through Successful Educational Actions, especially interactive groups and dialogic model of prevention and conflict resolution. These paths are presented as concrete possibilities, considering that they are already serving as a basis for work developed in the area, especially due to the validation they have in view of the improvement in learning and overcoming conflicts and violence.